Leksikon Perikanan di Kecamatan Mersam: Kajian Semantik - Rahadatul Aisy; Ernanda Ernanda; Anggi Triandana (Prodi Sastra Indonesia, FKIP Universitas Jambi, 2023)
Abstract This study aims to determine the lexicon form of fishing gear, catch, and means of transportation, and find out the lexical meaning of fisheries in Mersam District. This research uses a qualitative descriptive research method. The data collection techniques in this study were observation, interview, recording, and write, the data that gets in the form of words. Furthermore, the data that has been obtained will be analyzed using analytical techniques, namely by transcribing data, identifying, classifying, interpreting, and drawing conclusions.